Pathophysiology of the risk factors associated with osteoporosis and their correlation to the T-score value in patients with osteopenia and osteoporosis in the United Arab Emirates - Nihal A Ibrahim; Nessrin Nabil; Sana Ghaleb (Wolters Kluwer Medknow Publications, 2019)
Introduction: Osteoporosis is a growing major health problem with medical, social, and economic burden. The pathogenesis of osteoporosis involves excessive bone resorption by osteoclasts and decreased new bone formation by osteoblasts. Early diagnosis is the key to minimize the impact of osteoporosis on patients. Dual-energy X-ray absorptiometry at the hip or spine is the main standard test for measuring bone mineral density, and according to the World Health Organization, the T-score value of -2.5 or less determines osteoporosis. Aim: In this work, we aimed to study the risk factors associated with osteoporosis among a population sample of osteoporotic and controls in the United Arab Emirates (UAE) and relate them to the T-score value. Material and Methods: Two hundred male and female participants were recruited in the study. A questionnaire was used and data were correlated with the T-score value of the participants. Results: Results showed a positive correlation between the T-score value of the patients with osteoporosis and their calcium intake, exercise duration, and the age at menopause of female patients, whereas a negative correlation was evident between the T-score value and both caffeine and nicotine consumption. Results also revealed that patients with osteoporosis have significantly low body mass index, low calcium intake, and shorter duration of exposure to the sun than the control group. Conclusion: In conclusion, more intervention should be directed toward changing the modifiable risk factors in patients with osteoporosis and more studies should be directed toward osteoporosis in the UAE.